Сonstruction of the Sergeli Line of the Tashkent Metropolit - Azizovna, Hamrabaeva Nilufarkhan; Shuhratovna, Meslimova Pokizakhan (European Journal of Life Safety and Stability (2660-9630), 2022)
The article provides information about the new modern design and architectural solutions, the Tashkent subway on the line of Sergeli direction is located 6 stations on the overpass. A feature of the metro line in this area is that it is located on the overpass and consists of 6 stations